Zeald: From start-up to maturity. (August 2016) - Warren, Lorraine; Scahill, Shane
Zeald is a fast-growing website design, e-commerce and online marketing company in New Zealand, formed by three first-generation student entrepreneurs from the same family. The case tells the story of the start-up of the company, discussing the successes of the company and some of the challenges they met on the way. This case can help students understand the setbacks involved in growing a business from start-up to maturity, when even the best-laid plans can go astray. The study questions can help students consider how culture of this new 'family business' influences leadership, planning and marketing strategy.